Ecobrick Sebagai Solusi Multidimensi dalam Pengelolaan Sampah Plastik di Indonesia: Tinjauan Sistematis atas Aspek Sosial, Ekonomi, Teknologi, dan Pendidikan - Muda, Florianus Pruda (Jurnal Ekologi, Masyarakat dan Sains, 2025)
Plastic waste in Indonesia continues to increase and poses a complex environmental problem. Poor waste management leads to pollution and decreases the quality of life. Therefore, a solution is needed that is not only environmentally friendly but also integrates social, economic, technological, and educational aspects. This study aims to systematically review the potential of ecobricks as a multidimensional solution for plastic waste management. It analyzes 18 community service articles published between 2015 and 2025 from five national and international databases using a narrative-thematic synthesis method. The results show that ecobricks encourage community participation in waste management, open up economic opportunities through value-added products, and significantly reduce plastic waste volume. Technologically, ecobricks have sufficient strength for non-structural construction. In the education sector, ecobricks help improve environmental awareness and literacy among students and the general public. This study recommends strengthening local policies, continuous training, and further research to assess the durability of ecobricks in various environmental conditions.